Verbal Expression of Preparedness in Retirement Planning Interviews - Mahdysiuk, Liudmyla; Tryhub, Halyna; Duchiminska, Tamara; Kulchytska, Anna; Zasiekina, Larysa (Lesya Ukrainka Volyn National University, 2020)
Conceptualization of retirement requires interdisciplinary research, which is represented by psycholinguistic approach in the present paper. The study takes a first step to explore conceptualization of retirement by individuals with different levels of retirement preparedness. The study applies questionnaire Psychological Preparedness for Retirement (Zasiekina & Mahdysiuk, 2018) to assess levels of preparedness; semi-structured interviews to focus primarily on concerns related to planning postretirement period; Linguistic Inquiry and Word Count (LIWC) (Tausczik & Pennebaker, 2010) to reveal psychological categories and explore conceptualization of retirement. By the end of the assessment, data had been collected from 117 workers who were at preretirement period. The sample was weighted by age and occupation in order to improve its representative of the total population 22 (18.8%) – university staff, teachers at colleges, 18 (15.4%), nurses in kindergartens, 8 (6.6%), healthcare staff, 18 (15.4%), government officials, 28 (23.9%), workers from private sector, 23 (19.7%). The final weighted sample includes 65.8% females, average age 54.52, (SD=6.21). The results indicate that 8.5% respondents have a low level of preparedness, 61.5% - a medium level of preparedness and 30% - a high level of preparedness. Interestingly, the highest percentage of categories of affect and positive emotions were observed in the group with a medium level of preparedness, whereas the highest percentage of categories cause, focus on present, and family were captured in the group with a high level of preparedness. Taken together, these results suggest that the high level of retirement preparedness is associated with active cognitive reappraisal of retirement as a period of family activities.
Keywords: preparedness for retirement; retirement planned interviews; conceptualization; psychological meaning